The Unsolved Jigsaw Puzzle of the Immune Response in Chagas Disease - Acevedo, Gonzalo R.; Girard, Magalí C.; Gómez, Karina A. (Frontiers in Immunology, 2018)
Inside mammals, the intracellular and extracellular forms of T. cruzi are exposed to the different arms of the host's immune response (humoral and cell-mediated), but due to its urgency to stay alive and complete its life cycle, the parasite has developed efficient mechanisms to escape or manipulate this attack. This puzzling interplay between the host and the parasite allows both to coexist and evolve together, but not without harm to the former, since clinical manifestations of the infection can lead an individual into disability early in life. Several years of investigation have revealed the great complexity of host immune defenses against T. cruzi infection. This complexity emerges from its many components and their interactions with one another and with the parasite. The functionality of the immune cells and molecules is an aftereffect of the host’s genetic background, the diversity of parasite strains, the routes of infection, and the mechanisms used by T. cruzi to multiply and spread, as well as to evade and move away from the host’s immune surveillance. The expression of this scenario comprises different forms of response in the acute and chronic phases of infection. Furthermore, chronic Chagas disease is clinically diverse and this has been linked to parasite persistence and self-reactivity phenomena, driving a state of pathological inflammation in specific tissues. Many of the mechanisms of immunity against T. cruzi are fairly well understood, but unveiling the factors that lead each of these to success or failure, within the concerted response as a whole, requires further research. Here, we will provide an overview of the role deployed by the individual components of the innate and adaptive immune system, and the ways in which the parasite tampers with them. This review also intends to underline that the distinct components of the humoral and cell-mediated immunity are not independent, but function intimately and collectively during parasite infection to determine the quality and magnitude of each type of immune response.